In-situ modification of SiO2 coatings on steel plates for water repellent applications - Silvia, Linda; Mughayyirah, Yuniar; Sudarsono; Osman, Nurul Huda; Ramli, Muhammad Mahyiddin; Zainuri, Mochamad; Darminto (Discover, 2025)
This study investigates the in-situ modification of cristobalite SiO₂ (SC) coatings on steel plates to enhance surface properties, with a focus on developing hierarchical structures for water-repellent applications. SC was synthesized from silica sand via co-precipitation and combined with methyltrimethoxysilane through in-situ modification using sol-gel methods. Samples were prepared with varying SC concentrations of 0, 1.5, 3, 4.5, and 6 wt%. X-Ray Diffraction (XRD) characterization confirmed the coexistence of crystalline and amorphous phases, while Scanning Electron Microscope (SEM) indicated changes in particle size and morphology due to cristobalite SiO₂ addition. Fourier Transform Infra-Red (FTIR) analysis identified Si–O–Si asymmetric stretching bonds, and Atomic Force Microscope (AFM) demonstrated the formation of hierarchical micro-submicron structures with enhanced surface roughness. The roughness factor of the sample coatings was determined through calculations based on the AFM topographical data. Hydrophobicity analysis using water contact angle (WCA) measurements showed improved performance with increasing cristobalite SiO₂ content, achieving a maximum WCA of 132.6 ± 4.1° for the sample coated on a steel plate substrate. The best performance was observed at 6 wt% cristobalite SiO₂, as it significantly increased the water contact angle and thereby enhanced the hydrophobicity of the composite. The coated steel plates exhibited excellent hydrophobic properties, offering promising potential for practical applications in water-repellent technologies.